SDG#5 Gender Equality for Social Impacts via Transformations in Social Inclusion Strategies - Yeung, Shirley; Chu, Jamie (Journal of Ecohumanism, 2025)
The aim of this paper is to explore the elements of unnoticed areas from organizational culture and community perspective via the role of women in corporate structure and SDGxESG related activities for social impacts. By nurturing SDG related initiatives and empowering women communities, we can have more aspirations for the ways of improving ESG Score. A research was performed to analyze factors possibly related to CIIF Funded Projects (2020 Jan to 2025). One hundred thirty-eight articles published from 2020 to 2025 were discovered. By thoroughly delving into the articles, the top four factors: Implementation strategies on social inclusion, Service deliverables with behavioural changes,and Knowledge creation on social capital, and Measurable social impact.Through this paper, management of service organizations may explore the governance structure and decision-making process with the role of women with community engagement platform for social impacts.